An ecological investigation of Polish Olympic coaches' career pathways and their experiences of career transition to Olympic coaching roles - Darpatova-Hruzewicz, D.; Marek, P.; Kaminski, K. (International Sport Coaching Journal, 2025)
Most research on coaching adopts a Western, predominantly Anglo-Saxon, vantage point. This study sought to fill the gap in the literature by providing an Eastern European perspective on transition to high-performance coaching. Ten Polish Olympic coaches were interviewed to glean insights into their career pathways, cumulatively spanning the last three decades. First, using abductive analysis, three patterns of nonlinear career pathways were identified: teacher-track, club-coach track and athlete fast-track. Next, contextual and reflective thematic analyses were employed to examine the environmental constraints affecting role transitions. Consequently, drawing on Bronfenbrenner`s bioecological model, the Ecological Model for Coach Development was proposed to offer an alternative perspective on career transitions. The findings provide evidence for the situated and relational nature of career transitions as processes occurring in nested environmental contexts. We claim that advancing knowledge on transitions requires not only zooming into coaches` lived experiences of transitioning in/out of coaching roles, but also zooming out on macrolevel societal transformation processes, historically rooted values and belief systems, as well as mesolevel institutional constraints that steer career pathways and shape experiences. The study`s ecological orientation has the potential to enhance coaching education and practice by accounting for contextual complexity and temporality.